Feasibility of screening for preinjury frailty in hospitalized injured older adults. Issue 4 (April 2015) - Maxwell, Cathy A.; Mion, Lorraine C.; Mukherjee, Kaushik; Dietrich, Mary S.; Minnick, Ann; May, Addison; Miller, Richard S.
Abstract : BACKGROUND: Frailty assessment of injured older adults (IOAs) is important for clinical management; however, the feasibility of screening for preinjury frailty has not been established in a Level I trauma center. The aims of our study were to assess enrollment rates of IOAs and their surrogates as well as completion rates of selected brief frailty screening instruments. METHODS: We conducted a prospective cohort study on patients, age 65 years and older with a primary injury diagnosis. Patients and/or surrogates were interviewed within 48 hours of admission using the Vulnerable Elders Survey (VES-13), Barthel Index (BI), and the Life Space Assessment (LSA). Data analysis included frequency distributions, χ 2 statistics, Mann-Whitney and Kruskal-Wallis tests, and general linear modeling (analysis of variance). RESULTS: Of 395 admitted patients, 188 were enrolled with subsequent surrogate screening. Corresponding patient interviews were conducted for 77 patients (41%). Screening time was less than 5 minutes for each instrument, and item completion was 100%. Forty-two enrolled patients (22%) had nurse-reported delirium, and 69 (37%) patients either did not feel like answering questions or were unable to be interviewed secondary to their medical condition. The median score of surrogate responses for the VES-13 was 3.5 (interquartile range, 2–7), with 64% of the sample having a score of 3 or greater, indicating vulnerability or frailty. Median scores for the BI (19.0) and LSA (56.0) indicated high numbers with limitations in activities of daily living and limitations in mobilization. CONCLUSION: Screening for preinjury frailty in IOAs is feasible yet highly dependent on the presence of a surrogate respondent. A clinically significant percentage of patients have functional deficits consistent with frailty, dependence in activities of daily living, and limitations in mobilization. Implementation of validated brief screening instruments to identify frailty in clinical settings is warranted for targeting timely, efficient, and effective care interventions. LEVEL OF EVIDENCE: Epidemiologic study, level II.